Role of Human Resource Management (HRM) in Creating MSMEs’ Competitive Advantages in Kerinci Regency - Pajri, Mohd; Sesriyenti, Enny (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study examines the extent to which MSMEs fully utilize human resource management (HRM) to enhance competitiveness and adapt to dynamic market conditions. Methodology: Using a descriptive research method with a qualitative approach, the study incorporates a literature-based analysis of effective HR practices to assess their impact on MSME performance and sustainability. Results: The findings show that effective HRM practices, including skill development, work culture enhancement, and employee motivation, significantly influence MSME competitiveness. By leveraging strategic HRM, MSMEs can adapt to current circumstances and ensure long-term survival. Findings: This research highlights that HR serves as a cornerstone for MSME growth, enabling them to compete at local and national levels. Originality: The study offers a unique perspective on HRM's role in improving MSME competitiveness, particularly in the context of Kerinci Regency. Novelty: It addresses a gap in the literature by focusing on HRM as a critical factor in MSME sustainability and competitive advantage in emerging markets. Conclusions: Strategic HRM practices are crucial for enhancing MSME efficiency, employee satisfaction, and competitiveness. Collaboration among stakeholders is essential to realize MSMEs' growth potential. Type of Paper: Descriptive qualitative research paper.